Methylation metabolism in sepsis and systemic inflammatory response syndrome. (August 2013) - Semmler, Alexander; Prost, Jean-Christophe; Smulders, Yvo; Smith, Desiree; Blom, Henk; Bigler, Laurent; Linnebank, Michael
Abstract We have recently shown that sepsis leads to alterations of methylation metabolism in a rodent model. In this study we analyzed methylation metabolism and DNA methylation in human sepsis. Patients treated in one of the Intensive Care Units (ICU) at the University Hospital Bonn diagnosed with sepsis or systemic inflammatory response syndrome (n = 12) and patients who were treated due to traumatic brain injury, or stroke without clinical or laboratory signs of sepsis or major inflammation (n = 22) were included. Blood samples were taken two times a week, until ICU treatment was discontinued. Deproteinized plasma was used for simultaneous determination of the ubiquitous methyl-group donor S-adenosylmethionine (SAM) and its demethylated residue, S-adenosylhomocysteine (SAH), by using stable isotope dilution tandem mass spectrometry. Homocysteine (Hcys), hydrolyzation product of SAH, was determined by fully automated particle-enhanced immunonephelometry, and global DNA-methylation was measured by liquid chromatography tandem mass spectrometry. SAM (p < 0.001) and SAH (p < 0.001) plasma levels were higher in septic patients suggesting an increased cellular release of SAM and SAH in septic patients. The SAM/SAH ratio was decreased in septic patients (p = 0.002). There were no differences in homocysteine plasma levels (p = 0.32) or global leukocyte DNA methylation between septic and non-septic patients (p = 0.21) suggesting that sepsis-induced changes in methylation metabolism do not affect homocysteine plasma levels or the availability of SAM-derived methyl groups for DNA methylation. Sepsis and systemic inflammatory response syndrome induce considerable changes of methylation metabolism without apparent functional consequences on homocysteine plasma levels or DNA methylation. Further studies may explore the clinical relevance of the observed changes.